Synthesis and biological evaluation of new 3-substituted coumarin derivatives as selective inhibitors of human carbonic anhydrase IX and XII - Shaik Mahammad Ghouse; Kavyaraj Bahatam; Andrea Angeli; Gaurav Pawar; Krishna Kartheek Chinchilli; Venkata Madhavi Yaddanapudi; Arifuddin Mohammed; Claudiu T. Supuran; Srinivas Nanduri (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
The Carbonic anhydrase isoforms IX and XII play a significant role in regulating the intracellular and extracellular pH in hypoxic tumours abetting the metastasis of solid tumours. Selective and potent inhibitors targeting carbonic anhydrase IX and XII reduce the activity of these isoforms in hypoxic tumours, representing an antitumor and antimetastatic mechanism. Coumarin-based derivatives are selective inhibitors of CA isoforms IX and XII. In this study, we report the design and synthesis of new 3-substituted coumarin derivatives with different functional moieties and their inhibitory activity against various carbonic anhydrase isoforms. We found that the tertiary sulphonamide derivative 6c showed selective inhibition against CA IX with IC50 of 4.1 µM. Similarly, the carbothioamides 7c, 7b and oxime ether derivative 20a exhibited good inhibition against CA IX and CA XII. Additionally, the binding mode was predicted and validated using molecular docking and dynamic simulations.